2022
DOI: 10.1155/2022/9123332
|View full text |Cite|
|
Sign up to set email alerts
|

Research on Diagnosis Architecture of Cardiovascular Diseases Based on Multimedical Images

Abstract: Objective. To study the effect of a multi-image source 3D modeling imaging examination system on the diagnosis of cardiovascular diseases in cardiac surgery. Methods. The data of 680 confirmed patients and 1590 suspected patients in the cardiac surgery department of all hospitals of a large chain hospital management group were selected. All patients gave the examination results of multiple image sources and independent examination results of multiple image sources, respectively, their examination sensitivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Therefore, timely high-precision diagnostics of heart diseases, prevention and treatment at an early stage of the development of the disease acquire exceptional relevance. To improve the accuracy of diagnosing the state of the heart in recent decades, computer systems for automatic analysis [4][5][6] of electrocardiographic data obtained during the processing of an electrocardiographic signal have been widely used. Automatic analysis of electrocardiograms is a rather complex theoretical problem.…”
Section: Computational Methods Of the Cardiovascular Diseases Classif...mentioning
confidence: 99%
“…Therefore, timely high-precision diagnostics of heart diseases, prevention and treatment at an early stage of the development of the disease acquire exceptional relevance. To improve the accuracy of diagnosing the state of the heart in recent decades, computer systems for automatic analysis [4][5][6] of electrocardiographic data obtained during the processing of an electrocardiographic signal have been widely used. Automatic analysis of electrocardiograms is a rather complex theoretical problem.…”
Section: Computational Methods Of the Cardiovascular Diseases Classif...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%